The Use of Bahasa Indonesia among Sundanese Teenagers in Ciheleut-Bogor, West Java - Tita, Rostyana (LANTERN (Journal on English Language, Culture and Literature), 2017)
Sundanese is a langugae which is used in Bogor, West Java as cultural identity. The use of Sundanese in Bogor is greatly decreasing because of the use of Indonesian as the national langugae. This phenomenon also leads up the teenagers in Bogor to use Bahasa Indonesia rather than Sundanese. Therefore this research is purposed to find out the certain domain in using Bahasa Indonesia, and the factors that influence the use of Bahasa Indonesia. To get the accurate results, the research is done by collecting the questioner from the teenagers. The observation about what kind of language which is used by the teenagers also supports to get explanation in detail. Therefore, the research concludes that Bahasa Indonesia has replaces Sundanese, which is vernacular language in Bogor.  The research found out that the teenagers use Bahasa Indonesiain some certain domains. The factors that support the teenagers in using Bahasa Indonesia are their family, domain, attitudes, and the economic, social and political factors.